Description of Trichophoromyia macrisae, a new phlebotomine sand fly species (Diptera: Psychodidae) from Manu Biosphere Reserve, Peru - Méndez-Cardona, Sergio; Cabrera-Quintero, Olga L. (Zootaxa, 2024)
Phlebotomine sand flies are a highly diverse group of insects capable of transmitting Leishmania parasites. Therefore, the identification of vector species is important to understand local leishmaniasis dynamics. Among the Neotropical sand fly species, the genus Trichophoromyia is predominantly found in the Amazon. A new species of this genus, Trichophoromyia macrisae sp. nov., is described. Specimens were collected using Katchy light traps in forested areas of Manu Biological Station, located within the Manu Biosphere Reserve, in southern Peru. Morphological description was based on 10 male specimens. The disposition of setae in the gonocoxite and the shape of the paramere allows Th. macrisae sp. nov. to be distinguished from other species of genus that have aedeagal ducts > 4 times the length of the sperm pump. The description of Th. macrisae sp. nov. brings the number of species of Trichophoromyia in the Americas to 47 and in Peru to 15.